Formal vs. Informal CSR Strategies: Evidence from Italian Micro, Small, Medium-sized, and Large Firms - Russo, Angeloantonio (Journal of business ethics, 2009)
Recent research on corporate social responsibility (CSR) suggests the need for further exploration into the relationship between small and medium-sized enterprises (SMEs) and CSR. SMEs rarely use the language of CSR to describe their activities, but informal CSR strategies play a large part in them. The goal of this article is to investigate whether differences exist between the formal and informal CSR strategies through which firms manage relations with and the claims of their stakeholders. In this context, formal CSR strategies seem to characterize large firms while informal CSR strategies prevail among micro, small, and medium-sized enterprises. We use a sample of 3,626 Italian firms to investigate our research questions. Based on a multi-stakeholder framework, the analysis provides evidence that small businesses’ use of CSR, involving strategies with an important impact on the bottom line, reflects an attempt to secure their license to operate in the communities; while large firms rarely make attempts to integrate their CSR strategies into explicit management systems.